The significance of determining biomarkers of inflammation in chronic kidney failure - Petrović, Milica; Rabrenović, Violeta; Rančić, Nemanja (Vojnosanitetski pregled, 2024)
Background/Aim. Inflammation is the main cause of the onset, progression, and outcome of chronic kidney disease (CKD). The aim of the study was to examine the predictive value of inflammatory biomarkers in patients with CKD stages I–V and their association with parameters characteristic of CKD. Methods. A cross-sectional study analyzed 117 adult patients with CKD who were divided into two groups according to the glomerular filtration rate (GFR): Group 1, with normal to mild impairment of renal function (GFR ≥ 60 mL/min/1.73 m2), stages I and II, and Group 2 with moderate and severe impairment of renal function (GFR < 60 mL/min/1.73 m2), stages III, IV, and V, who have not started dialysis treatment. In addition to standard laboratory analyses, we determined derived parameters in patients, neutrophil-lymphocyte ratio (NLR), platelet- lymphocyte ratio (PLR), systemic immune-inflammation index (SII), and system inflammation response index (SIRI), as markers of inflammation. Results. A statistically significant difference between Groups 1 and 2 was observed for body mass index (p < 0.003), for platelets, hemoglobin, creatinine, urea, acidum uricum, iron, phosphorus, parathyroid hormone, and proteinuria 24 hrs (p < 0.001), for calcium (p
Keywords: biomarkers; glomerular filtration rate; inflammation; renal insufficiency, chronic